БИОФАРМАЦЕВТИЧЕСКИЕ СВОЙСТВА БАКТЕРИОФАГОВ, АКТИВНЫХ В ОТНОШЕНИИ SALMONELLA ENTERICA SEROVAR ABORTUSOVIS, ВЫДЕЛЕННЫХ В УСЛОВИЯХ КАЗАХСТАНА - Р. Саттарова; Е. Оспанов; М. Маталипова; Ж. Тлегенова; А. Нурпейсова; М. Касенов; К. Боранбаева; Н. Пименов; Г. Спиридонов (Animal Health and Biosafety, 2026)
Bacteriophage therapy for bacterial infections is based on the ability of lytic bacteriophages to selectively eliminate pathogenic microorganisms. The mechanism of action involves two key stages: the penetration of the phage into a susceptible bacterial cell followed by its destruction (lysis), accompanied by the release of newly formed viral particles. Understanding the interactions between bacteriophages, bacteria, and host tissues is of critical importance from both ecological and pharmacological perspectives. The successful development and application of phage-based therapeutics require comprehensive investigation of their pharmacokinetic properties and pharmacodynamic properties, which determine the efficacy and safety of phage therapy. This study presents the biopharmaceutical characteristics of a Salmonella Abortusovis bacteriophage isolated at the Kazakh Scientific Research Veterinary Institute. The LD₅₀ of the Salmonella Abortusovis 17NS strain was determined to be 1,5х10³ colony-forming units (CFU). Pharmacokinetic studies conducted in laboratory animals demonstrated that the highest phage titers were achieved within 2–24 hours after administration, while complete elimination of the phage from the host occurred within 6–48 hours. Phage plaques were detected in the liver, kidneys, spleen, and intestinal contents during the first 24 hours after administration. Pharmacodynamic evaluation of the Salmonella Abortusovis bacteriophage revealed peak phage concentrations at 4 hours post-administration, followed by a gradual decline over the subsequent 48–72 hours. Two hours after administration, phages were detected in the heart (1х10⁴ PFU), liver (2х10⁶ PFU), and spleen (1х10³ PFU). By 4 hours, a marked increase in plaque-forming units (PFU) was observed, reaching 2,1х10⁸ PFU in the heart, 1х10⁷ PFU in the liver, and 1,1х10⁵ PFU in spleen tissue. After 48 hours, the number of phage particles had decreased substantially, and by the third day, no phages were detected in any examined tissues. The bacteriophages recovered from the experimental animals retained their specificity toward the indicator bacterial culture.